A dynamic nonlinear model for a once-through boiler-turbine unit in low load. (October 2019) - Niu, Yuguang; Du, Ming; Ge, Weichun; Luo, Huanhuan; Zhou, Guiping
Highlights: The characteristics of units in low load are considered in the model establishment. The model structure is improved by considering the dynamics in the turbine section. The proper expression of feed water enthalpy is derived in this paper. Parameter estimation is carried out with consideration of variable coal quality. The model is validated by a 600 MW once-through unit in low load. Abstract: Under the background of serious wind and solar energy curtailment in China, flexibility modification of coal-fired supercritical units is selected as an effective technical path to provide space for renewable energy into the grid. Modeling of coordinated control system in low load has yet to be conducted to date. In this work, a simplified dynamic model for coal-fired once-through boiler-turbine unit aimed at low load working condition is built up. First, the major model structure is established mainly based on mass and energy balance laws as well as thermodynamic equilibrium of important parameters combined with the analysis of operation characteristics. Then, the unknown parameters in the model are estimated by regression analysis, statistical analysis, and nonlinear optimization algorithm. Comparison results between measurement and simulation results show that the model has acceptable accuracy and, importantly, also captures the essential dynamic characteristics of units.